Experiment and numerical simulation of cavitation performance on a pressure-regulating valve with different openings. Issue 4 (15th January 2015) - Qu, W S; Tan, L; Cao, S L; Xu, Y; Huang, J; Xu, Q H
Abstract: As a kind of widely used device in pipe system for pressure and flow rate regulating, the valve would experience cavitation in the case when a sharp pressure drop occurs, which will induce the energy loss, noise and vibration of pipeline system, and even operational accidents. The experiment on flow resistance coefficient of a DN600 pressure-regulating valve under operation conditions from 0% to 100% openings is conducted. Based on the RNG k-e turbulence model and the Rayleigh-Plesset cavitation equation, a set of computational model is developed to simulate the turbulent flow in the valve under operational conditions from 0% to 100% openings. The computational results of flow resistance coefficient are compared to the experimental data. And the numerical simulation is employed to predict the cavitation performance of the valve at different inlet flow conditions. The transient cavitating flow is calculated to reveal the time evolution of cavitation in the valve.